Novelty: Nursing scholars’ guide for successful publication - Joko Gunawan; Yupin Aungsuroch; Mary L Fisher; Colleen Marzilli (Belitung Raya Foundation, Indonesia, 2022)
The “pressure” or “passion” to publish is a common reality in academia. All faculty are required to demonstrate that they are engaged in research and that their work is disseminated in reputable journals. However, writing manuscripts is quite challenging; some papers for publication may take days, weeks, months, and even years. This editorial aims to provide the editors’ points of view to assist authors in successful acceptance and publication in an international nursing journal.